Diet, gut microbiota and cognition - Cicely Proctor (2018)
ï¿½ 2016, Springer Science+Business Media New York. The consumption of a diet high in fat and sugar can lead to the development of obesity, type 2 diabetes mellitus (T2DM), cardiovascular disease and cognitive decline. In the human gut, the trillions of harmless microorganisms harboured in the host’s gastrointestinal tract are called the ‘gut microbiota’. Consumption of a diet high in fat and sugar changes the healthy microbiota composition which leads to an imbalanced microbial population in the gut, a phenomenon known as “gut dysbiosis”. It has been shown that certain types of gut microbiota are linked to the pathogenesis of obesity. In addition, long-term consumption of a high fat diet is associated with cognitive decline. It has recently been proposed that the gut microbiota is part of a mechanistic link between the consumption of a high fat diet and the impaired cognition of an individual, termed “microbiota-gut-brain axis”. In this complex relationship between the gut, the brain and the gut microbiota, there are several types of gut microbiota and host mechanisms involved. Most of these mechanisms are still poorly understood. Therefore, this review comprehensively summarizes the current evidence from mainly in vivo (rodent and human) studies of the relationship between diet, gut microbiota and cognition. The possible mechanisms that the diet and the gut microbiota have on cognition are also presented and discussed.